Entrepreneurial Intentions and Business Performance: A Study of Women Entrepreneurs in Telangana - Shukla, Mohini; Bhatt, Alka Singh; Chandramouli, S.; Mohan, Shefali; Rai, Anjali (International Review of Management and Marketing, 2025)
This study explores the relationship between entrepreneurial intentions and business performance among women entrepreneurs in Telangana, India. Despite increasing institutional support and targeted policy initiatives, women-led enterprises in the region continue to underperform compared to their male counterparts. Drawing upon the Theory of Planned Behavior, this research examines the mediating role of entrepreneurial intentions in the relationship between five key factors—access to finance, entrepreneurial education, family support, government support policies, and risk-taking propensity—and business performance. Using a quantitative cross-sectional design, data were collected from 603 women entrepreneurs through a structured questionnaire. The findings, analyzed through structural equation modeling, indicate that entrepreneurial intentions significantly mediate the effects of family support and risk-taking propensity on business performance. Access to finance negatively influences both intentions and outcomes, while entrepreneurial education and government support policies do not show significant impact. The study underscores the importance of psychological and relational drivers over institutional mechanisms in enhancing women’s entrepreneurial success and offers practical recommendations for designing gender-sensitive support programs.